Answer:
ur airpods are broken if the case and 1 ear aint working
Step-by-step explanation:
Answer:
do your self use your brain picture turmtottgejs s
Step-by-step explanation:
ײ8;49☆☆(3) swcond equqtio
Step-by-step explanation:
(a + b)² = 9
(b + c)² = 25
(a + c)² = 81
Taking the square root:
a + b = ±3
b + c = ±5
a + c = ±9
By adding these three equations together and dividing both sides by 2, we get the value of a + b + c.
Possible combinations for a + b + c such that the sum is greater than or equal to 1 are:
a + b + c = (-3 + 5 + 9)/2 = 11/2
a + b + c = (3 − 5 + 9)/2 = 7/2
a + b + c = (3 + 5 + 9)/2 = 17/2
Answer:
Step-by-step explanation:
Rate of change = (2-3.6)/(5-(-3)) = -1.6/8 = 0.2
Answer:
.18
Step-by-step explanation:
if ^2 is an exponent
(-16t*-16t)+8t+48
(258t+8t)+48
266t+48
48/266
.180
or .18